Development of an Innovative Dual Construct for Targeted Drug Delivery in the Oral Cavity - Elena Mazzinelli; Ilaria Favuzzi; Marianna Messina; Giorgia Fratocchi; Federica Vincenzoni; Eleonora Santo Stefano; Francesco Cecconi; Carlo Lajolo; Alessia Basco; Raffaella Castagnola; Massimo Cordaro; Francesco Scilla; et al. (Pharmaceutics)
Background: Oral lichen planus (OLP) is a chronic autoimmune disease of the oral mucosa, classified among potentially malignant oral disorders (OPMDs). It is characterized by keratinocyte apoptosis and persistent inflammation. Standard treatments involve topical corticosteroids administered via mouthwashes, gels, or ointments, but these require frequent application, have limited retention, and may cause side effects. To address these limitations, this study aimed to develop an innovative dexamethasone delivery system targeting the oral cavity, based on poly(lactic acid) (PLA) fibers coated with chitosan (CS) and poly(lactic-co-glycolic acid) (PLGA) nanoparticles. Methods: CS-coated PLA fibers were characterized for their mucoadhesive and cytocompatibility properties, while PLGA nanoparticles were analyzed for size, shape, encapsulation efficiency, cellular uptake, drug release efficiency, and cytocompatibility. Results: Both polymers demonstrated cytocompatibility, and chitosan-coated PLA fibers exhibited mucoadhesive properties. PLGA nanoparticles were effectively internalized by the cells and successfully released the drug into the cytoplasm. The combination of CS-coated PLA fibers and PLGA nanoparticles provided dual benefits: mucoadhesion and efficient cellular uptake, even under conditions simulating salivation. Conclusions: These findings highlight the potential of the proposed system to improve mucoadhesive drug delivery. Further optimization is needed to enhance patient compliance and therapeutic efficacy.